39.9k views
4 votes
Which steps can be used to verify that tan(w + Pi) = tan(w)?

2 Answers

4 votes

Answer:

D. Rewrite tan(w + Pi) using the tangent sum identity. Then simplify the resulting expression using tan(Pi) = 0.

Explanation:

test on edge

Which steps can be used to verify that tan(w + Pi) = tan(w)?-example-1
User Vibol
by
5.8k points
0 votes

Answer:

D. proves
tan(w + \pi) = tanw

Explanation:

Given


tan(w + \pi) = tan(w)

See attachment for complete question

Option D answers the question (See proof below).

Using tangent sum identity, we have:


tan(A + B) = (tanA + tanB)/(1 - tanAtanB)

In this case:


A = w


B = \pi

So, we have:


tan(w + \pi) = (tanw + tan \pi)/(1 - tanw. tan \pi)

Note that


tan\ pi = 0

So:


tan(w + \pi) = (tanw + tan \pi)/(1 - tanw. tan \pi)


tan(w + \pi) = (tanw + 0)/(1 - tanw * 0)


tan(w + \pi) = (tanw)/(1)


tan(w + \pi) = tanw

Hence: Option D answers the question

Which steps can be used to verify that tan(w + Pi) = tan(w)?-example-1
User JCLaHoot
by
5.6k points